Planning Analysis of the Upper Structure of the Disaster Logistics Warehouse of BPBD Bantul Regency with SAP2000 - Adam Sulton; Sely Novita Sari; Rizal Maulana (Universitas Islam Raden Rahmat, Malang, 2025)
Indonesia is a country that is very vulnerable to natural disasters, especially earthquakes, because of its position in the Pacific Ring of Fire region. Bantul Regency, Yogyakarta, is one of the earthquake-prone areas that requires disaster-resistant infrastructure, including disaster logistics warehouses as emergency logistics storage and distribution centers. This study aims to analyze the upper structure of the disaster logistics warehouse of BPBD Bantul Regency to be more optimal and earthquake-resistant using SAP2000 software. The secondary data used is technical data ranging from soil type, earthquake zone, dead load, live load, and earthquake load, which are analyzed according to SNI 1726:2019 and SNI 1729:2020 standards. The results showed that the steel profiles used were IWF 350x175x11x7 for the rafter, IWF 200x150x9x6 for front and rear regels, IWF 250x125x9x6 for side regels, and HB 300x300x18x10 for columns. It was found that the regel was unstable due to the failure to withstand lateral loads, but overall, the upper structure of the warehouse worked optimally according to the results of the check design and steel stress check.